Kesiapan Bencana Terhadap Zonasi Bahaya Erupsi Gunung Api Ile Lewotolok - Making, Valentina Wua; Sunimbar, Sunimbar; Rahmawati, Arfita (Jurusan Pendidikan Geografi FKIP Universitas Halu Oleo, 2026)
Settlement relocation is a crucial step in protecting communities from the risk of natural disasters, especially in areas prone to volcanic eruptions. The objectives of this study are to: 1) determine the condition of settlements before and after relocation in Lamawolo Village; and 2) determine the disaster mitigation in Lamawolo Village before and after relocation, Ile Ape Timur District, Lembata Regency. The research method used is a qualitative method where data is collected from primary and secondary data sources through observation, interviews, and documentation. Data analysis used is the interpolation technique and the Miles and Hubermen Interactive model (1992). The results of the study show that: 1) the Lamawolo Village settlement before relocation was in zone III of a high-level disaster-prone area, with a distance of 10 km from Ile Lewotolok Volcano, with a steep to very steep slope. Meanwhile, the new settlement in Tanah Merah after relocation is in a low-level danger zone with a distance of 17 km with a flat slope; 2) Disaster mitigation before relocation was carried out through evacuation based on the socialization of evacuation routes by the Lembata Regency Regional Disaster Management Agency. The impact of the Ile Lewotolok Volcano eruption affected 138 families, with 6 seriously injured, 2 slightly injured, and 2 fatalities. After relocation, mitigation focused on saving the remaining results of the disaster, such as agricultural and livestock. Based on the results of the evaluation and observation, the Tanah Merah location was declared safe for relocation and became a new place for the community.